Antarctic ascidians: an isolated and homogeneous fauna - Primo, Carmen; Vázquez, Elsa (Polar Research, 2009)
Several biogeographical studies have already been performed on the ascidians of the Antarctic region. However, new data obtained in the last few years have led us to a revision of the biogeography of this fauna. To examine the biogeographical structure of the Antarctic region, we divided it into 10 sectors, depending on the principal geographical features, and then applied cluster analysis and a multi-dimensional scaling ordination to a presence/absence matrix of species for each biogeographical area. Our study shows that Antarctic ascidians are a very homogeneous fauna, with a high level of endemism in the whole region (25–51% of Antarctic endemic species per sector), but with a low percentage of sector endemism (only up to 10%). This probably results from isolation arising from the Antarctic Convergence, and the vast geographical distances from adjacent regions, as well as from the relative constancy of the hydrographical conditions and the dispersal of organisms through circumpolar currents. In fact, cosmopolitan species represented only 0–7% of the total ascidian fauna in all sectors. Only the Bellingshausen Sea (low sample size), Bouvetøya (young and isolated, with an impoverished ascidian fauna) and the South Sandwich Islands (also young and isolated) are relatively separated. The insular sectors were more closely related to the South America and sub- Antarctic regions than the continental ones, showing a latitudinal gradient.
Keywords: Sørishavet; biogeografi; fauna; sekkdyr; zoogeografi

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern